Safety maximization of percutaneous transthoracic needle biopsy with ultrasound guide in subpleural lesions in the evaluation of pulmonary consolidation - Sperandeo, Marco (Respir Res, 2019)
The study by Kiranantawat et al. “Clinical role, safety and diagnostic accuracy of percutaneous transthoracic needle biopsy in the evaluation of pulmonary consolidation” highlights how “pulmonary consolidation can be safely evaluated with CT-guided percutaneous needle biopsy”. Even if we agree about the role of CT guidance, we would like to point out how Thoracic Ultrasound could be better than CT for biopsy of subpleural lesions that could easily be detected and reached with this “real-time” and quicker technique.